Analysis of mathematical problem solving ability students of junior high school to Polya model - Kaliky, S H; Nurlaelah, E; Jupri, A (Journal of physics. Conference series, 2019)
This research aims to analyze the mathematical problem solving ability of students on the subject of the triangle. This research used descriptive qualitative method and involved 35 students in grade 8 at a junior high school. The instrument is way a written test consisting of three items of problem solving. Analysis was conducted according to Polya model. This study showed that the problem solving ability of students still in a weak category. It is seen from the weak ability of students to understand the problem, devise a plan to solve problems, execute plans problem solving, and verification. Besides plant the lack of mathematical problem solving ability of students can be seen from the test results of students who received an average score that is well below the average problem-solving abilities.